Prevention of pathogen transmission during ultrasound use in the Intensive Care Unit: Recommendations from the College of Intensive Care Medicine Ultrasound Special Interest Group (USIG). Issue 2 (29th May 2020) - Costello, Cartan; Basseal, Jocelyne M; Yang, Yang; Anstey, James; Yastrebov, Konstantin
Abstract: ICU ultrasonography constitutes important part of modern car patient care. Current standards and practice of infection control and prevention are inadequate. This purpose of this document is to adapt and expand the 2017 Australasian Society for Ultrasound in Medicine (ASUM) and the Australasian College for Infection Prevention Control (ACIPC) guidelines on minimum standards for reprocessing/cleaning of ultrasound transducers to the specifics of intensive care medicine and provide advice to the ICU practitioners and health care administrators. It considers the medical, administrative, financial and practical controversies surrounding implementation, and addresses emerging issues of care for patients with confirmed or suspected Corona Virus Disease 2019 (COVID‐19).